COMPARISON OF THE DNA CAPTURE PERFORMANCE OF THE FABRICATED NOVEL MICROCHIP AND FTA® PAPER FOR HUMAN BLOOD SAMPLES (Journal of Forensic Medicine & Toxicology, 2023)
Development of miniaturized devices for analytical processes has been a progressive trend over several decades. The immense potential for implementation of such devices in the form of “Lab-on-a-chip” technology was demonstrated. “Lab-on-a-chip” (LOC) devices in the form of membranes or beads have been fabricated as an advanced technique for DNA extraction, offering fast analysis, minimal sample requirement and no contamination. The present study reports fabrication of a polymer based Microchip offering rapid and low cost extraction of DNA from blood samples in a short time. The Microchip was prepared by introducing a disc of fusion 5-filter paper between two Poly (methyl methacrylate) (PMMA) layers where the activated polymer substrate acted as a solid DNA binding phase. DNA extraction from human blood was carried out on a Microchip using an alkaline extraction method and quantitated using RT-PCR followed by amplification and STR genotyping. The DNA binding capability of the fabricated Microchip was evaluated and compared with the FTA® paper by measuring the concentration of DNA in the final elutes using RT-PCR. On-chip DNA extraction suggests that the DNA holding capacity of the fabricated Microchip was better than the FTA® paper. The efficiency of the fabricated microchip for DNA isolation from blood, refractory to DNA concentrations in the elute is significant as compared to FTA® paper. The device is cost effective and efficient; therefore, it is expected to succeed in cases where DNA quantity is low.
Keywords: On-chip method; PMMA(Poly methyl methacrylate); Fusion-5- filter paper; Plasma treatment; APTES functionalization; Highest DNA capturing and FTA® paper